2008
DOI: 10.4269/ajtmh.2008.79.245
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Echinococcus multilocularis Originating from a Patient with Alveolar Echinococcosis Occurring in Minnesota in 1977

Abstract: To date, only a single proven case of autochthonous human alveolar echinococcosis has been recorded in Minnesota in 1977. At that time, echinococcal lesions removed from the patient were experimentally inoculated into voles, and the parasite materials obtained from the voles were preserved as histopathologic specimens for 30 years. In this study, retrospective genetic analysis of larval Echinococcus multilocularis originating in the human case was performed using the histopathologic specimens. DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…Outside Alaska, only one autochthonous case in the United States is reported from a resident of Minnesota in 1977(Gamble et al, 1979 who was subsequently identified as the N2, or central North American, haplotype Yamasaki et al, 2008). This is the first and only report of zoonotic transmission of the N2 haplotype endemic to the NCR; there was no evidence of exposure in a serological survey of high risk people (trappers) in the United States region of the NCR (Hildreth et al, 2000).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 86%
“…Outside Alaska, only one autochthonous case in the United States is reported from a resident of Minnesota in 1977(Gamble et al, 1979 who was subsequently identified as the N2, or central North American, haplotype Yamasaki et al, 2008). This is the first and only report of zoonotic transmission of the N2 haplotype endemic to the NCR; there was no evidence of exposure in a serological survey of high risk people (trappers) in the United States region of the NCR (Hildreth et al, 2000).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 86%
“…This fi nding may be caused by the long incubation time required for clinical manifestation in humans (12) or a strain of E. multilocularis with a low zoonotic potential. Although there is little evidence of human risk from the strain of E. multilocularis in central North America (14), a human case caused by this strain has been confi rmed (15).…”
Section: Resultsmentioning
confidence: 99%
“…Only two infections have been reported in humans in central North America, one of which was confirmed as the N2 central North American strain (James and Boyd 1937; Gamble et al 1979;Yamasaki et al 2008). In contrast, the global incidence of human alveolar hydatid disease is around 18,000 new cases per year, with most occurring in Asia (91%) and Europe (Torgerson et al 2010).…”
mentioning
confidence: 99%